Risk Factors of Spontaneous Abortion - Dinda Rizki Nawawi; Iman Ruansa; Mariana Mariana (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Spontaneous abortion is defined as a pregnancy loss at the gestational age of under 20 weeks or within the first trimester, which is usually marked by intravaginal bleeding and expulsion of conceptus through the cervix. In 20% of pregnancies, vaginal bleeding occurs prior to 20 weeks of gestational age, and 50% of these cases develop into spontaneous abortion. More than 80% of spontaneous abortion occurs before 12 weeks of gestational age. There are many factors contributing to the incidence of spontaneous abortion such as prior miscarriage and maternal age. Several chronic diseases are also known to trigger spontaneous abortion, such as diabetes and autoimmune diseases. Immediate postpartum conception and infections, such as cervicitis, vaginitis, HIV, syphilis and malaria are also common risk factors. In some cases, fetal chromosomal abnormalities may also cause spontaneous abortion. Environmental contaminants such as arsenic, lead, and organic solvents are thought to be factors that may induce spontaneous abortion.